2015
DOI: 10.1002/bdd.1940
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of omeprazole and phenacetin first‐pass metabolism in humans using a microscale bioreactor and pharmacokinetic models

Abstract: A new in vitro microfluidic platform (integrated insert dynamic microfluidic platform, IIDMP) allowing the co-culture of intestinal Caco-2 TC7 cells and of human primary hepatocytes was used to test the absorption and first-pass metabolism of two drugs: phenacetin and omeprazole. The metabolism of these drugs by CYP1A2, CYP2C19 and CYP3A4 was evaluated by the calculation of bioavailabilities and of intrinsic clearances using a pharmacokinetic (PK) model. To demonstrate the usefulness of the device and of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…54 Similarly, human hepatocytes, maintained in the microfluidic LiverChip TM system showed differentiated tissue structures and cytochrome P450 (CYP)-dependent activities over seven days of culture. 55 In further approaches, microfluidic devices were used with various combinations of cell types and ECM components, such as co-culture of hepatocytes with intestinal cells for investigations of drug adsorption and metabolism, 56 hepatocyte culture in a collagen sandwich configuration with flow characteristics, 57 or using de-cellularized scaffolds as a physiological matrix for cell maintenance under dynamic conditions. 58,59 The need for both efficient medium and oxygen transfer to the cells while allowing 3D tissue assembly is addressed by a dynamic four-compartment 3D bioreactor technology for high-density liver cell culture.…”
Section: Dynamic 3d Culture Technologies and Bioreactor Approachesmentioning
confidence: 99%
“…54 Similarly, human hepatocytes, maintained in the microfluidic LiverChip TM system showed differentiated tissue structures and cytochrome P450 (CYP)-dependent activities over seven days of culture. 55 In further approaches, microfluidic devices were used with various combinations of cell types and ECM components, such as co-culture of hepatocytes with intestinal cells for investigations of drug adsorption and metabolism, 56 hepatocyte culture in a collagen sandwich configuration with flow characteristics, 57 or using de-cellularized scaffolds as a physiological matrix for cell maintenance under dynamic conditions. 58,59 The need for both efficient medium and oxygen transfer to the cells while allowing 3D tissue assembly is addressed by a dynamic four-compartment 3D bioreactor technology for high-density liver cell culture.…”
Section: Dynamic 3d Culture Technologies and Bioreactor Approachesmentioning
confidence: 99%
“…In particular, interactions between the gut and the liver have been the focus of intense research (Chen et al, ; Choe, Ha, Choi, Choi, & Sung, ; D. W. Lee, Ha, Choi, & Sung, ). For example, Leclerc et al, developed a microfluidic gut–liver chip to study the first‐pass metabolism of drugs (Bricks et al, ; Prot et al, ). Similarly, van Midwoud, Merema, Verpoorte, and Groothuis () reported a perfusion culture device for gut and liver tissue slices, and observed the interaction between the two tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated a functional coculture system that could be utilized to examine intestinal absorption and liver metabolism of drugs, including acetaminophen (Figure B). Other studies have also been conducted using multi‐OCC technology to mimic oral drug intake . For example, Maschmeyer et al utilized a coculture system to observe troglitazone intake, a drug that was withdrawn from the market as a result of liver toxicity in humans.…”
Section: Current Organ‐on‐a‐chip Platformsmentioning
confidence: 99%